PROBLEMS OF BIOLOGY LEARNING PROCESSES AT NATIONAL AND INTERNATIONAL LEVELS: A SYSTEMATIC LITERATURE REVIEW - Paraniti, Anak Agung Inten; Arjaya, Ida Bagus Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
The increase of learning attainments always pursued through processes of reflection, evaluation, and refinement. Refinement of learning is conducted based on challenges occured since learning taken place. Present study is conducted to analyse variety of problems in the processes of biology learning at senior high school through systematic literature reviews to national and international accredited journals by performing PRISMA approach (Preffered Reporting Item for Systematic Review and Meta-Analysis). Researchers select published articles from year 2018 to 2021 by using keywords “problems of biology learning”, “obstacles of biology learning”, and “biology learning obstacles in high school” by exploring google scholar, ERIC and springer. Exclusion and inclusion criteria resulted in 10 from 535 articles. This study contributes as guidance for teachers, researchers, and policy makers since they need scientific information regarding problems of biology learning at senior high school level as a basis for formulating strategies of creative, effective, and innovative pedagogies. Present study shows that problems of biology learning at senior high school in national dan international levels consist of three main factors, thse are a) human resource factor in terms of teachers and students; b) content factor, namely subject to be learned by students; c) learning facility factor; and d) family factor